Sociocultural variation in attitudes toward use of genetic information and participation in genetic research by race in the United States: implications for precision medicine. (16th March 2016) - Dye, Timothy; Li, Dongmei; Demment, Margaret; Groth, Susan; Fernandez, Diana; Dozier, Ann; Chang, Jack
Abstract: Background "Precision medicine" (PM) requires researchers to identify actionable genetic risks and for clinicians to interpret genetic testing results to patients. Whether PM will equally benefit all populations or exacerbate existing disparities is uncertain. Methods We ascertained attitudes toward genetic testing and genetic research by race in the United States using the online Amazon mTurk US workforce (n = 403 White; n = 56 African American (AA)). Generalized linear models were used to test differences in beliefs and preferences by race, adjusting for sociodemographics and prior genetic experience. Results AA were less likely than White to believe that genetic tests should be promoted or made available. Further, AA were less likely to want genetic testing results or to participate in genetic research. Conclusions Important dimensions that underlay PM are not universally accepted by all populations. Without clear attention to concerns, AA communities may not equally benefit from the rapidly-emerging trend in PM-centered research and clinical practice.